Bioconversión de flavonoides cítricos utilizando células microbianas enteras - Hernández Guzmán, Christian (Universidad Autónoma Metropolitana, 2015)
The objective of this study was to evaluate the bioconversion of citrus flavonoid naringenin to be enriched compounds and hydroxylated and / or methoxylated using whole microbial cells using. Through a "screening" four strains were selected for Yarrowia lipolytica 2.2ab expressing for bioconversion activity of the molecule naringenin. The "screening" was performed at the micro scale serological jars with solid medium for growth and subsequently carry out the process of biconversión. Identifying enriched flavonoids, hydroxylated produced during a process of bioconversion by whole microbial cells on a surface culture, was performed by high performance liquid chromatography coupled to mass performance (HPLC-MS). Production of the hydroxy compound (C15H12O6) at 48 h of bioconversion was observed; already from 192 h other compounds were identified. Furthermore the regio-selectivity in the hydroxylation was evaluated using three different systems: water phase, two-phase (aqueous-organic) and organic phase. The regio-selectivity can be useful for modification of biological flavonoids to develop and produce new drugs. It was observed that the strain Y. lipolytica 2.2ab presents the appropriate enzyme system to achieve the bioconversion of naringenin to hydroxylated products. Y. lipolytica is capable of expressing the enzyme cytochrome P450 monooxygenase, which has been studied by having the ability to perform oxidation of different xenobiotic compound. Moreover, P450 enzymes are potential candidates to perform the regio-selective hydroxylation of a large number of compounds.; El objetivo de este trabajo fue evaluar la bioconversión del flavonoide cítrico naringenina a compuestos enriquecidos ya sean hidroxilados y/o metoxilados utilizando células microbianas enteras empleando. A través de un “screening” con cuatro cepas, se seleccionó a Yarrowia lipolytica 2.2ab por expresar actividad para realizar la bioconversión de la molécula de naringenina. El “screening” se llevó a cabo a nivel micro escala en frascos serológicos con medio sólido para su crecimiento y posteriormente llevar a cabo el proceso de bioconversión. La identificación de los flavonoides enriquecidos, hidroxilados producidos durante un proceso de bioconversión por células microbianas enteras en un cultivo superficial, se realizó por cromatografía de líquidos de alta resolución acoplada a masas (HPLC-MS). Se observó la producción del compuesto hidroxilado (C15H12O6) a las 48 h de bioconversión; y a partir de las 192 h se identificaron otros compuestos. Además se evaluó la regio-selectividad en la hidroxilación utilizando tres sistemas diferentes: fase acuosa, bifásico (acuoso-orgánico) y fase orgánica. La regio-selectividad puede ser útil para la modificación biológica de flavonoides para desarrollar nuevos fármacos. Se observó que la cepa Y. lipolytica 2.2ab presenta el sistema enzimático adecuado para lograr la bioconversión de naringenina a productos hidroxilados. Y. lipolytica es capaz de expresar la enzima monooxigenasa citocromo P450, la cual ha sido estudiada por tener la capacidad de llevar a cabo la oxidación de diferentes compuestos xenobióticos. Además, las enzimas P450 son potenciales candidatos para llevar a cabo la hidroxilación regio-selectiva de una gran cantidad de compuestos.